2020
DOI: 10.1021/acsami.0c01539
|View full text |Cite
|
Sign up to set email alerts
|

Fusiform-Like Copper(II)-Based Metal–Organic Framework through Relief Hypoxia and GSH-Depletion Co-Enhanced Starvation and Chemodynamic Synergetic Cancer Therapy

Abstract: The therapeutic effect of traditional chemodynamic therapy (CDT) agents is severely restricted by their weakly acidic pH and glutathione (GSH) overexpression in the tumor microenvironment. Here, fusiform-like copper­(II)-based tetrakis­(4-carboxy phenyl)­porphyrin (TCPP) nanoscale metal–organic frameworks (nMOFs) were designed and constructed for the first time (named PCN-224­(Cu)-GOD@MnO2). The coated MnO2 layer can not only avoid conjugation of glucose oxidase (GOD) to damage normal cells but also catalyzes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(117 citation statements)
references
References 64 publications
1
116
0
Order By: Relevance
“…Based on this, a fusiform-like nanoscale MOF (nMOF, named PCN-224(Cu)-GOx@MnO 2 ) was reported by Yang et al (Figure 4a). [57] The nMOF is composed of Cu 2+ , tetrakis(4-carboxy phenyl)porphyrin (TCPP) ligands, and GOx and MnO 2 coated. In their structure design, the coated MnO 2 layer acts as a gatekeeper to avoid the conjugated GOx to damage normal cells and as a nanozyme to catalyze the generation of O 2 from H 2 O 2 to promote the oxidation of Glu by GOx.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, a fusiform-like nanoscale MOF (nMOF, named PCN-224(Cu)-GOx@MnO 2 ) was reported by Yang et al (Figure 4a). [57] The nMOF is composed of Cu 2+ , tetrakis(4-carboxy phenyl)porphyrin (TCPP) ligands, and GOx and MnO 2 coated. In their structure design, the coated MnO 2 layer acts as a gatekeeper to avoid the conjugated GOx to damage normal cells and as a nanozyme to catalyze the generation of O 2 from H 2 O 2 to promote the oxidation of Glu by GOx.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Recently, Zhang et al reported the black Reproduced with permission. [57] Copyright 2008, American Chemical Society. b) Schematic illustration of the design of FeCysPW@ZIF-82@CAT Dz.…”
Section: Other Nanomaterials-based Chemodynamic Agentsmentioning
confidence: 99%
“…ROS can destroy tumor cells through multifactorial mechanisms, including oxidizing the biological macromolecules, destroying angiogenesis to cut off the supply of nutrients to tumor cells [ 36 , 37 ]. Typically, five therapeutic strategies including radiation therapy [ [38] , [39] , [40] , [41] ], chemodynamic therapy [ [42] , [43] , [44] , [45] , [46] ], sonodynamic therapy [ [47] , [48] , [49] , [50] ], bioreductive chemotherapeutics (e.g., tirapazamine, TPZ) [ [51] , [52] , [53] , [54] ], and photodynamic therapy (PDT) [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ] can generate ROS. Among all these approaches, PDT-based cancer therapies have been extensively exploited.…”
Section: Reactive Oxygen Species-based Antitumor Therapymentioning
confidence: 99%
“…Cu‐based chemical‐driven ROS‐ECBs, such as Cu 2+ ‐doped biomaterials (Li et al, 2019; Liu et al, 2019a; Wang et al, 2019), copper sulfide (Pan et al, 2020; Wang et al, 2020), and Cu 2‐ x Se (Wang, Guo, et al, 2020), exhibited excellent performance in CDT compared with Fe‐based chemical‐driven ROS‐ECBs. It has been reported that the Cu + ‐catalyzed Fenton‐like reaction with the high reaction rate could occur in a wider range of pH compared with Fe 2+ (Wang et al, 2020).…”
Section: Energy‐converting Biomaterials For Cancer Therapymentioning
confidence: 99%